Engineered stem cell exosomes for oral and maxillofacial wound healing - Hao, Ming; Duan, MengNa; Yang, Zhijing; Zhou, Hengzong; Li, Shuangji; Xiang, Jingcheng; Wu, Han; Liu, Huimin; Chang, Lu; Wang, Dongxu; Liu, Weiwei (Frontiers in Bioengineering and Biotechnology, 2022)
Because wound healing of the oral and maxillofacial region affects patients’ quality of life and mental health, effective therapies are needed to promote wound healing. However, traditional treatment methods have limited efficacy. Exosomes secreted by stem cells used for oral and maxillofacial wound healing demonstrate outstanding effects. Stem cell-derived exosomes carry the regenerative and repair ability of stem cells. Moreover, they have good biosafety and avoid tumorigenesis risk. Nevertheless, it is limited to applying natural stem cell exosomes due to low yield, impurity, lack of targeting, and low drug delivery rate. Multiple modification methods have been developed to engineered stem cell exosomes with beneficial properties such as modifying parent cells and directly processing stem cell exosomes, including co-incubation, genetic engineering, electroporation, ultrasound, and artificial synthesis of engineered stem cell exosomes. These engineered stem cell exosomes can carry nucleic acids, proteins, and small molecules, giving them anti-inflammatory and cell proliferation regulatory abilities and enabling the targeted promotion of efficient soft tissue repair after trauma. Engineered stem cell exosomes can reduce inflammation, promote fibroblast proliferation and angiogenesis, and reduce scar formation to promote oral and maxillofacial wound healing, including diabetic and burn wounds. Altogether, engineered stem cell exosomes are an effective treatment that shows potential in oral and maxillofacial wound healing.